Aplikasi Analisis Multivariat Kovarian Untuk Menguji Efektifitas Metode Pembelajaran Qiroah dan Kalam - Ajeng Wahyuni (LP. Ma'arif Janggan Magetan, 2022)
Teaching Arabic has various challenges and problems. Teachers, Methods, out-of-date resources, and the low interest of students are also a problem. One way to deal with these challenges is to create attractive learning designs. The purpose of the study was to find the most effective method used in learning Qiraah and Kalam between the JIGSAW and the CIRC methods. This study is a quantitative study using Multivariate Covariance Analysis (MANCOVA) with the school origin as a control variable. Respondents in this study were students of SMA MBS Al-Amin Seputih Banyak in 2018. The study results show that the JIGSAW method is generally more effective in learning Qiraah and Kalam than the CIRC method.